Myocardial Ischemia in Severe Aortic Regurgitation Despite Angiographically Normal Coronary Arteries - (:unkn) unknown (TOHOKU UNIV MEDICAL PRESS, 2012)
Patients with severe aortic regurgitation frequently present with angina pectoris. The exact pathophysiology for angina in aortic regurgitation is not clear. Left ventricular hypertrophy and myocardial blood supply-demand mismatch have been the suggested mechanisms to explain ischemia. However, no conclusive clinical study exists to define the incidence of ischemia in patients with severe aortic regurgitation and normal coronary arteries. We, therefore, investigated the frequency of myocardial ischemia in relation to left ventricular hypertrophy or dilatation in patients with severe aortic regurgitation and normal coronary arteries. We reviewed the medical records of all patients (n = 311) with aortic valve replacement due to aortic regurgitation between 2007 and 2010. We selected subjects with normal coronary arteries (n = 182) for the study purpose, and we identified 35 patients who underwent myocardial perfusion scintigraphy prior to the coronary angiography (19 female and 16 male subjects; age 45.0 +/- 8.9 years). Left ventricular hypertrophy and dilatation were detected in 9 (26%) and 5 (14%) patients, respectively. Myocardial perfusion scintigraphy showed evidence of ischemia in 10 (29%) patients with normal coronary arteries. The presence of ischemia did not relate to the presence of left ventricular hypertrophy and/or dilatation. As a potential mechanism, aortic regurgitation causes backflow of blood from the aorta into the left ventricle, hence disturbs coronary flow dynamics. In conclusion, myocardial ischemia is common (nearly one-third) among patients with severe aortic regurgitation even in the absence of coronary obstruction, left ventricular hypertrophy and/or dilatation.
Keywords: aortic valve regurgitation; coronary angiography; myocardial ischemia; myocardial perfusion scintigraphy; normal coronary arteries; DOPPLER-ECHOCARDIOGRAPHIC ASSESSMENT; BLOOD-FLOW; ANGINA-PECTORIS; RECOMMENDATIONS; DAMAGE